Innovative Higher Education - Major, Claire; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Innovative Higher Education is a refereed scholarly journal that strives to package fresh ideas in higher education in a straightforward and readable fashion. The four main purposes of Innovative Higher Education are: (1) to present descriptions and evaluations of current innovations and provocative new ideas with relevance for action beyond the immediate context in higher education; (2) to focus on the effect of such innovations on teaching and students; (3) to be open to diverse forms of scholarship and research methods by maintaining flexibility in the selection of topics deemed appropriate for the journal; and (4) to strike a balance between practice and theory by presenting manuscripts in a readable and scholarly manner to both faculty and administrators in the academic community.
Keywords: Higher education; Higher Education